Development and democratization through cooperatives A study on the San Juanico Farmers Producers Cooperative and the impact to its rural society. - Camenforte, Camille Lorraine E. (Camille Lorraine E. Camenforte, 2009)
A cooperative is a duly registered association of persons with a common bond of interest, who have voluntarily joined together to achieve a lawful common social or economic end, making equitable to contribution to the capital required and accepting a fair share of the risks and benefits of the undertakings in accordance with universally accepted cooperative principle. Organizing a cooperative can both be complex and simple. It requires, first of all an understanding of the basic needs of the perspectives cooperative members. It demands patience from the co-organizer who must take the cooperative goal and objectives, its visions and long term goals a real part of the members lives. But it can be also easy because the Cooperative Code of the Philippines (RA 6938) has devised very clean cut steps for the coop-organizer and members. However, despite the vast research on Philippine Cooperatives, little is known about the true nature of a Cooperative. These forms of organizations have now evolved into mechanisms which brings empowerment to the community. Our objective is to identify to assess the efficacy of the cooperative system democratization and development in the society through of the indicators, Self-reliance, sustainability, participation and autonomy.